A Study On Normal Stress In an Infinite Elastic Body With A Locally Curved Carbon Nanotube - Alan, Kadriye Simsek (AMER INST PHYSICS, 2019)
In this study, the results of normal stress values in unidirectional fibrous composite with locally curved carbon nanotube (CNT) were obtained as much as the second approximation and the obtained results were analyzed. For these investigations, were used in the frame of the piecewise homogeneous body model the three-dimensional geometrically nonlinear exact equations of elasticity theory. The boundary value problem is solved by using boundary form perturbation method. For simplicity, a small carbon nanotube is considered and interaction between the carbon nanotubes is not into account. Numerous results are obtained for the normal stress distribution and the effect of the problem parameters on this stress distribution is analyzed.
Keywords: Carbon Nanotube; stress distribution; geometric nonlinearity; locally curved; Mathematics; Physics